The epidemiology of malpractice claims in primary care: a systematic review. Issue 7 (18th July 2013) - Wallace, E; Lowry, J; Smith, S M; Fahey, T
Abstract : Objectives: The aim of this systematic review was to examine the epidemiology of malpractice claims in primary care. Design: A computerised systematic literature search was conducted. Studies were included if they reported original data (≥10 cases) pertinent to malpractice claims, were based in primary care and were published in the English language. Data were synthesised using a narrative approach. Setting: Primary care. Participants: Malpractice claimants. Primary outcome: Malpractice claim (defined as a written demand for compensation for medical injury). We recorded: medical misadventure cited in claims, missed/delayed diagnoses cited in claims, outcome of claims, prevalence of claims and compensation awarded to claimants. Results: Of the 7152 articles retrieved by electronic search, a total of 34 studies met the inclusion criteria and were included in the narrative analysis. Twenty-eight studies presented data from medical indemnity malpractice claims databases and six studies presented survey data. Fifteen studies were based in the USA, nine in the UK, seven in Australia, one in Canada and two in France. The commonest medical misadventure resulting in claims was failure to or delay in diagnosis, which represented 26–63% of all claims across included studies. Common missed or delayed diagnoses included cancer and myocardial infarction in adults and meningitis in children. Medication error represented the second commonest domain representing 5.6–20% of all claims across included studies. The prevalence of malpractice claims in primary care varied across countries. In the USA and Australia when compared with other clinical disciplines, general practice ranked in the top five specialties accounting for the most claims, representing 7.6–20% of all claims. However, the majority of claims were successfully defended. Conclusions: This review of malpractice claims in primary care highlights diagnosis and medication error as areas to be prioritised in developing educational strategies and risk management systems.